Regioselective Radical Reaction of Monometallofullerene Y@C2v(9)-C82 With N-arylbenzamidine Mediated by Silver Carbonate - Li, Jia; Yu, Pengyuan; Lai, Peng; Zou, Jiajun; Liu, Zhe; Yi, Xiuguang; Wang, Wei; Pan, Changwang (Frontiers in Chemistry, 2020)
A novel radical reaction of monometallofullerene Y@C2v(9)-C82 with N-arylbezamidine (1) is successfully conducted through catalysis with silver carbonate. The high-performance liquid chromatographic and mass spectrum results demonstrate that the reaction is highly regioselective to afford only one mono-adduct (2) with an imidazoline group added on C82 cage, and computations through density functional theory reveal the addition group is attached to a specific [5, 6]-bond (C20-C76) near the Y atom. Furthermore, the analysis of prymidalization angle of the carbon atoms demonstrates the geometry of carbon cage is in favor of the regioselective formation of isomer (20, 76).